The Effect of Problem-Based Learning Model on Students' Mathematical Problem-Solving Ability SMP Negeri 2 Bandar Petalangan - Parindang, Edwin Amanu; Abdurrahman, Abdurrahman (Indonesian Journal of Teaching and Learning, 2025)
This study aims to determine the effect of the Problem-Based Learning model on the mathematical problem-solving ability. This study is a quantitative study with a quasi-experimental research type and a non-equivalent control group design. The population in this study was all students of class VIII of SMP Negeri 2 Bandar Petalangan, while the sample in this study amounted to 40 students, consisting of 2 classes, with a saturated sampling technique, meaning that all members of the population were used as samples. Data were collected using test sheets by conducting pretests and posttests, then analyzed using descriptive statistical analysis techniques and inferential statistical analysis with the SPSS program. The results showed that the Problem-Based Learning model had a significant effect on students' mathematical problem-solving abilities, with a Sig. value of 0,014 (0,014 <0,05). So it can be concluded that there is a significant influence of the Problem-Based Learning model on the Mathematical Problem-Solving Ability.